SEISMIC SCATTERING AT THE TOP OF THE MANTLE TRANSITION ZONE - Thybo H.; Nielsen L.; Perchuc E. (My University, 2003)
We document strong seismic scattering from around the top of the mantle Transition Zone in all available high resolution explosion seismic profiles from Siberia and North America. This seismic reflectivity from around the 410 km discontinuity indicates the presence of pronounced heterogeneity in the depth interval between 320 and 450 km in the Earth's mantle. We model the seismic observations by heterogeneity in the form of random seismic scatterers with typical scale lengths of kilometre size (10-40 km by 2-10 km) in a 100-140 km thick depth interval. The observed heterogeneity may be explained by changes in the depths to the alpha-beta-gamma spinel transformations caused by an unexpectedly high iron content at the top of the mantle Transition Zone. The phase transformation of pyroxenes into the garnet mineral majorite probably also contributes to the reflectivity, mainly below a depth of 400 km, whereas we find it unlikely that the presence of water or partial melt is the main cause of the observed strong seismic reflectivity. Subducted oceanic slabs that equilibrated at the top of the Transition Zone may also contribute to the observed reflectivity. If this is the main cause of the reflectivity, a substantial amount of young oceanic lithosphere has been subducted under Siberia and North America during their geologic evolution. Subducted slabs may have initiated metamorphic reactions in the original mantle rocks.